Neuronal differentiation in the adult hippocampus recapitulates embryonic development - Esposito, Maria Soledad (2005)
In the adult hippocampus and olfactory bulb, neural progenitor cells generate neurons that functionally integrate into the existing circuits. To understand how neuronal differentiation occurs in the adult hippocampus, we labeled dividing progenitor cells with a retrovirus expressing green fluorescent protein and studied the morphological and functional properties of their neuronal progeny over the following weeks. During the first week neurons had an irregular shape and immature spikes and were synaptically silent. Slow GABAergic synaptic inputs first appeared during the second week, when neurons exhibited spineless dendrites and migrated into the granule cell layer. In contrast, glutamatergic afferents were detected by the fourth week in neurons displaying mature excitability and morphology. Interestingly, fast GABAergic responses were the latest to appear. It is striking that neuronal maturation in the adult hippocampus follows a precise sequence of connectivity (silent → slow GABA → glutamate → fast GABA) that resembles hippocampal development. We conclude that, unlike what is observed in the olfactory bulb, the hippocampus maintains the same developmental rules for neuronal integration through adulthood.